Rational Design of an α-1,3-fucosyltransferase for the Biosynthesis of 3-Fucosyllactose in Bacillus Subtilis Atcc 6051a Via de Novo Gdp-L-Fucose Pathway - Blamey-Alegria, J (American Chemical Society, 2024)
3-Fucosyllactose (3-FL) is an important oligosaccharide and nutrient in breast milk that can be synthesized in microbial cells by α-1,3-fucosyltransferase (α-1,3-FucT) using guanosine 5’-diphosphate (GDP)-l-fucose and lactose as substrates. However, the catalytic efficiency of known α-1,3-FucTs from various sources was limited due to their low solubility. To enhance the microbial production of 3-FL, the efficiencies of α-1,3-FucTs were evaluated and in Bacillus subtilis (B. subtilis) chassis cells that had been endowed with a heterologous synthetic pathway for GDP-l-fucose, revealing that the activity of FucTa from Helicobacter pylori (H. pylori) was higher than that of any of other reported homologues. To further improve the catalytic performance of FucTa, a rational design approach was employed, involving intracellular evaluation of the mutational sites of M32 obtained through directed evolution, analysis of the ligand binding site diversity, and protein structure simulation. Among the obtained variants, the FucTa-Y218 K variant exhibited the highest 3-FL yield, reaching 7.55 g/L in the shake flask growth experiment, which was 3.48-fold higher than that achieved by the wild-type enzyme. Subsequent fermentation optimization in a 5 L bioreactor resulted in a remarkable 3-FL production of 36.98 g/L, highlighting the great prospects of the designed enzyme and the strains for industrial applications. © 2024 American Chemical Society